Study on Glycemic Statusand Oxidative Stress Level in Patients of Type 2 Diabetes Mellitus With and Without Retinopathy: A Teaching Hospital Based Study - Rachana Gahlawat; Dinesh Narain Saksena (Asian Journal of Medical Research, 2020)
Background: Diabetes is a chronic disease and sustained hyperglycemia attacks both micro vessels and macro vessels throughout the body. It is the leading cause of retinopathy, nephropathy, end-stage renal disease, non traumatic lower extremity amputations.Subjects and Methods:Twenty five (25) Patients with newly diagnosed type 2 diabetes mellitus without any signs of retinopathy were identified from outpatient services of department of Medicine and Twenty five (25) Patients with newly diagnosed type 2 diabetes mellitus with retinopathy were identified from outpatient services of department of Ophthalmology along with 25 healthy subjects were taken as controls. Diabetic retinopathy was diagnosed after doing detailed dilated fundoscopic examination as per the standard criteria.Results:The levels of FBS, HbA1c, total cholesterol, triglycerides and MDA were significantly higher in the diabetics without retinopathy, while the HDL and Vitamin C levels were lower as compared to those of the control group. The levels of FBS HbA1c, cholesterol, triglycerides and MDA were significantly higher in the diabetics with retinopathy, while the HDL and Vitamin C levels were lower as compared to those in the diabetes without retinopathy.Conclusion: The increased oxidative stress and a decreased antioxidant status can predict the micro-vascular complications in diabetes mellitus. The raised MDA levels indicate the oxidative stress and the decreased Vitamin C levels indicate the reduced antioxidant status in diabetic retinopathy.